Interactive effect of brassinolide and lime on growth and yield of maize (Zea mays L.) on acid soils of South-East Nigeria. Issue 22 (16th December 2018) - Otie, Victoria; Ping, An; Eneji, Egrinya
ABSTRACT: Our aim was to determine the combined effect of brassinolide (BR) and lime on the growth and yield of maize on acid soils of South East Nigeria using two BR levels (0 and 250 mL), two maize varieties [Ikom White (IKW) and Oba-98] and two lime levels (0 kg ha −1 and 500 kg ha −1 ). The IKW was better ( P  ≤ 0.05) in growth morphology than Oba-98; however, Oba-98 was more (p ≤ 0.05) efficient in intercepting radiation (420.16 μmol m −2 s −1 ) than IKW (325.08 μmol m −2 s −1 ). The 500 kg ha −1 lime plus BR improved ( P  ≤ 0.05) nitrogen (N) uptake, dry matter yield, harvest index, shoot to root ratio, and grain yield, especially in Oba-98. Thus, the interactive action of BR and lime could increase the soil pH to an extent for enhanced yield of hybrid maize.